Synthesis and Application of Hydride Silica Composites for Rapid and Facile Removal of Aqueous Mercury. Issue 18 (20th November 2013) - Katok, Kseniia V.; Whitby, Raymond L. D.; Fayon, Franck; Bonnamy, Sylvie; Mikhalovsky, Sergey V.; Cundy, Andrew B.
Abstract The adsorption of ionic mercury(II) from aqueous solution on functionalized hydride silicon materials was investigated. The adsorbents were prepared by modification of mesoporous silica C‐120 with triethoxysilane or by converting alkoxysilane into siloxanes by reaction with acetic acid. Mercury adsorption isotherms at 20 °C are reported, and maximum mercury loadings were determined by Langmuir fitting. Adsorbents exhibited efficient and rapid removal of ionic mercury from aqueous solution, with a maximum mercury loading of approximately 0.22 and 0.43 mmol of Hg g−1 of silica C‐120 and polyhedral oligomeric silsesquioxane (POSS) xerogel, respectively. Adsorption efficiency remained almost constant from pH 2.7 to 7. These inexpensive adsorbents exhibiting rapid assembly, low pH sensitivity, and high reactivity and capacity, are potential candidates as effective materials for mercury decontamination in natural waters and industrial effluents.